2019
DOI: 10.1177/2048004019869736
|View full text |Cite
|
Sign up to set email alerts
|

Is high-density lipoprotein a modifiable treatment target or just a biomarker for cardiovascular disease?

Abstract: Epidemiological data strongly support the inverse association between high-density lipoprotein cholesterol concentration and cardiovascular risk. Over the last three decades, pharmaceutical strategies have been partially successful in raising high-density lipoprotein cholesterol concentration, but clinical outcomes have been disappointing. A recent therapeutic class is the cholesteryl ester transfer protein inhibitor. These drugs can increase circulating high-density lipoprotein cholesterol levels by inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that larger HDL particles seem to protect against atherogenesis, while the smaller subclasses are positively correlated with the risk of CVD [19,[34][35][36][37][38][39][40][41][42][43][44]. When measuring HDL-C by traditional methods, the positive and negative associations of small and large HDL particles may counteract each other.…”
Section: Hdl-subfractionsmentioning
confidence: 99%
“…Previous studies have shown that larger HDL particles seem to protect against atherogenesis, while the smaller subclasses are positively correlated with the risk of CVD [19,[34][35][36][37][38][39][40][41][42][43][44]. When measuring HDL-C by traditional methods, the positive and negative associations of small and large HDL particles may counteract each other.…”
Section: Hdl-subfractionsmentioning
confidence: 99%
“…Furthermore, in the past decade, several studies have shown that extremely high HDL-C is associated with elevated mortality [12][13][14][15][16]. Additionally, increased HDL-C owing to the use of cholesteryl ester transfer protein (CETP) inhibitors does not protect against the incidence of cardiovascular disease or mortality [32][33][34][35]. Although genetic variation in CETP is a major determination for high HDL-C in Japan [36,37], such genetic information was not investigated in this study.…”
Section: Discussionmentioning
confidence: 94%
“…For the last decade, several trials to raise HDL-C concentrations pharmacologically by inhibiting the cholesteryl ester transfer protein were mostly unsuccessful in the prevention of CVD [13,14,15], suggesting that some factors beyond HDL-C concentration per se may be responsible for the increased risks of CVD. In the current results, the underlying mechanism between extremely high HDL-C and impaired glucose metabolism, a well-known risk for CVD, remains unknown, although participants with extremely high HDL-C levels had favorable profiles for weight, lipids, exercise, and smoking.…”
Section: Discussionmentioning
confidence: 99%